Discontinuous double-shell domes through Islamic eras in the middle east and central Asia: History, morphology, typologies, geometry, and construction - Ashkan, M.; Ahmad, Y. (Kim Williams Books, 2010)
This paper presents a developed geometric approach for deriving the typologies and geometries of discontinuous double-shell domes in Islamic architecture. Common geometric attributes are created using a corpus of twenty one domes that were built in the Middle East and Central Asia, beginning from the early through to the late Islamic periods. An outline of the origin and development of the discontinuous double-shell domes and their morphological features are addressed. Using the al-Kashi geometrical essences, a four-centered profile as an initial shape is constructed based on new geometric parameters to deduce the geometric commonalities of the two aspects of formal language (typologies and geometries) of such domes. Common geometric prototypes for typical profiles shared by the study cases are generated and formulated according to a proposed system. The theoretical frame work for the formal language of discontinuous double-shell dome architecture is structured to indicate a moderate development of this sort of Islamic domes and highlight the specific geometric relationship between the Islamic domical configurations and practical mathematic rules for many decades. It can also be established a basic approach for considering the geometric compositional designs and the typological derivations of the other eastern domes.